Visual literacy: does it enhance leadership abilities required for the twenty-first century?. Issue 2 (2nd April 2016) - Bintz, Carol
Abstract: The twenty-first century hosts a well-established global economy, where leaders are required to have increasingly complex skills that include creativity, innovation, vision, relatability, critical thinking and well-honed communications methods. The experience gained by learning to be visually literate includes the ability to see, observe, analyze, describe and interpret-leading to honing critical thinking skills, visual communications, problem-solving and the ability to articulate your thoughts both verbally and visually. This qualitative research explores the potential benefits to leaders in being visually literate.